2021
DOI: 10.1177/23328584211039787
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Arrests and Educational Impacts: Linking ICE Arrests to Declines in Achievement, Attendance, and School Climate and Safety in California

Abstract: With increased tensions and political rhetoric surrounding immigration enforcement in the United States, schools are facing greater challenges in ensuring support for their students of immigrant and Latinx origin. This study examined the associations between county-level immigration arrests and academic achievement, absenteeism, and measures of school climate and safety for students in the California CORE districts. Using ordinary least squares regression analyses with year, grade, school, and student fixed ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Consistent with prior research (Bellows, 2021; Kirksey, 2020; Kirksey & Sattin‐Bajaj, 2021; Kirksey et al., 2020), we observed a substantial spike of nearly 15 percentage points in COI student daily absence rates in the week immediately following the raid in Hamblen County, and an estimated 33 percent increase in the monthly absence rate in the raid month compared to average absence rates in prior Aprils. Our estimate of the immediate increase in student absences is closer in magnitude to that of Kirksey (2020), who specifically investigated incidents involving high numbers of immigration arrests.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with prior research (Bellows, 2021; Kirksey, 2020; Kirksey & Sattin‐Bajaj, 2021; Kirksey et al., 2020), we observed a substantial spike of nearly 15 percentage points in COI student daily absence rates in the week immediately following the raid in Hamblen County, and an estimated 33 percent increase in the monthly absence rate in the raid month compared to average absence rates in prior Aprils. Our estimate of the immediate increase in student absences is closer in magnitude to that of Kirksey (2020), who specifically investigated incidents involving high numbers of immigration arrests.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the second level of Dreby's (2012) pyramid of children's burdens represents the repercussions of persistent fear among children who live with unauthorized family members, which includes approximately 5 to 6 million children, of whom greater than 80 percent are U.S. citizens. An expanding body of research associates the protracted fear and stress these children endure with poorer health outcomes and academic performance, more school absences, and lower socio-emotional well-being (Amuedo-Dorantes & Lopez, 2015;Brabeck & Xu, 2010;Kirksey & Sattin-Bajaj, 2021;Kirksey et al, 2020;Yoshikawa, 2011). Hainmueller et al (2017) showed that, alternatively, when protecting immigrant mothers from the fear and stress of deportation through the Deferred Action for Childhood Arrivals (DACA) program, their children had 50 percent fewer diagnoses of adjustment and anxiety disorder.…”
Section: Evidence Base On the Consequences Of Immigration Enforcement...mentioning
confidence: 99%
See 3 more Smart Citations